Boundary behavior of ring Q-homeomorphisms in metric spaces - Smolovaya, E. S. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We investigate the problem of extension of so-called ring Q-homeomorphisms between domains in metric spaces with measures to the boundary. We establish conditions for the function Q(x) and the boundary of the domain under which any ring Q-homeomorphism admits a continuous or a homeomorphic extension to the boundary. The results are applicable, in particular, to Riemannian manifolds, Löwner spaces, and Carnot and Heisenberg groups.